Transformações Metabólicas de Agrotóxicos em Peixes: Uma Revisão - Santana, Lígia Maria Borges Marques; Cavalcante, Rivelino Martins (Orbital: The Electronic Journal of Chemistry, 2016)
Fish are among the organisms most damaged by aquatic contamination by pesticides, being ecologically relevant for their bioaccumulation and biomagnification skills of contaminants, which may present health risks to fish consumers. Several sublethal damages are known in fish due pesticide exposure, however, the mechanisms acting on their bioaccumulation, toxicity and elimination process are not yet fully understood. This paper reviewed basic concepts of bioaccumulation of pesticides in fish, including chemical behavior that drives their bioaccumulation, and major metabolic transformation processes in fish (absorption and elimination pathways, primary organs, enzymatic groups, phases and chemical reactions involved in biotransformations). We exemplified metabolites generated from reactions of detoxification and bioactivation (when the metabolite is more toxic than the parent compound) of organophosphates, carbamates and pyrethroids, commonly used as pesticides worldwide. Understanding the metabolic transformations of pesticides in organisms beyond the target species for which it was developed, is critical to elucidate the effects of toxicity on an ecosystem, grounding risk prevention actions to keep environmental quality, that includes health hazards of aquatic organisms and human.DOI: http://dx.doi.org/10.17807/orbital.v8i4.856